Role of maternal occupational physical activity and psychosocial stressors on adverse birth outcomes. Issue 3 (6th October 2016) - Lee, Laura J; Symanski, Elaine; Lupo, Philip J; Tinker, Sarah C; Razzaghi, Hilda; Chan, Wenyaw; Hoyt, Adrienne T; Canfield, Mark A
Abstract : Objectives: We examined the association of an array of estimated maternal occupational physical activities and psychosocial stressors during pregnancy with odds for preterm birth (PTB) and small-for-gestational age (SGA). Methods: Data for infants born without major birth defects delivered from 1997 to 2009 whose mothers reported working at least 1 month during pregnancy were obtained from the National Birth Defects Prevention Study. We linked occupational codes to the US Department of Labor's Occupational Information Network, which provides estimates of exposure for multiple domains of physical activity and psychosocial stressors by occupational categories. We conducted factor analysis using principal components extraction with 17 occupational activities and calculated factor scores. ORs for PTB and SGA across quartiles of factor scores in each trimester were computed using logistic regression. Results: Factor analysis grouped occupational domains into 4 groups based on factor loadings. These groups were 'occupational physical activity', 'interpersonal stressor', 'automated work' and 'job responsibility'. High levels of 'occupational physical activity' were significantly associated with SGA (adjusted OR (AOR) for highest quartile compared with lowest quartile of factor score: 1.36; 95% CIs 1.02 to 1.82; p for trend=0.001) and were also positively associated with PTB (AOR: 1.24; 95% CI 0.93 to 1.64; p for trend=0.01). No clear results were observed across domains of psychosocial stressors. Conclusions: Our findings expand understanding of associations between occupational physical activity and psychosocial stressors and PTB and SGA and suggest that additional research is needed to further examine these relationships.